2022
DOI: 10.3389/fcvm.2022.840358
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ApoC3 Paradoxically Aggravates Atherosclerosis in Hamsters With Severe Refractory Hypercholesterolemia

Abstract: RationaleApoC3 plays a central role in the hydrolysis process of triglyceride (TG)-rich lipoproteins mediated by lipoprotein lipase (LPL), which levels are positively associated with the incidence of cardiovascular disease (CVD). Although targeting ApoC3 by antisense oligonucleotide (ASO), Volanesorsen markedly reduces plasma TG level and increase high-density lipoprotein cholesterol (HDL-C) in patients with hypertriglyceridemia (HTG), the cholesterol-lowering effect of ApoC3 inhibition and then the consequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…This finding may be related to flavonoids being phytoestrogens, and there is a relationship between estrogen and lipid levels (59)(60)(61). Previous studies found that ApoC3 has a vital role in the lipoprotein lipase-mediated hydrolysis of triglyceride-rich lipoproteins, and knockdown of the ApoC3 gene significantly lowered triglyceride levels and elevated HDL cholesterol levels in hypertriglyceridemic patients (62). Estrogen inhibits ApoC3 expression, thereby reducing triglyceride levels (63).…”
Section: Discussionmentioning
confidence: 98%
“…This finding may be related to flavonoids being phytoestrogens, and there is a relationship between estrogen and lipid levels (59)(60)(61). Previous studies found that ApoC3 has a vital role in the lipoprotein lipase-mediated hydrolysis of triglyceride-rich lipoproteins, and knockdown of the ApoC3 gene significantly lowered triglyceride levels and elevated HDL cholesterol levels in hypertriglyceridemic patients (62). Estrogen inhibits ApoC3 expression, thereby reducing triglyceride levels (63).…”
Section: Discussionmentioning
confidence: 98%
“…1 ). The ability of APOC3 to prevent LPL’s action could explain why in a very hypertriglyceridemic LDLR-deficient hamster model, APOC3-deficiency, despite lowering plasma triglycerides, resulted in increased atherosclerosis ( 51 ); it is possible that increased LPL-mediated hydrolysis of TRL triglycerides brought about by APOC3-deficiency might have resulted in increased atherogenic remnant formation.…”
Section: Apoc3 Pools and Lipid Metabolismmentioning
confidence: 99%
“…Under a high-cholesterol diet, these rabbits similarly exhibited reduced atherosclerosis as well as lower total cholesterol levels compared to wild-type rabbits [ 44 ]. Recent work from Xu et al on ApoC3 deficiency in LDLR-deficient hamsters suggests that loss of ApoC3 may paradoxically accelerate the atherosclerotic phenotype observed in LDLR-deficient hamsters on a high-cholesterol diet [ 129 ]. Further investigation on the effects and benefits of APOC3 inhibition in different animal models of atherosclerosis need to be carried out.…”
Section: Genome Editing Approaches For Coronary Artery Diseasementioning
confidence: 99%